2021
DOI: 10.7554/elife.63352
|View full text |Cite
|
Sign up to set email alerts
|

Local circuit allowing hypothalamic control of hippocampal area CA2 activity and consequences for CA1

Abstract: The hippocampus is critical for memory formation. The hypothalamic supramammillary nucleus (SuM) sends long-range projections to hippocampal area CA2. While the SuM-CA2 connection is critical for social memory, how this input acts on the local circuit is unknown. Using mice, we found that SuM axon stimulation elicited mixed excitatory and inhibitory responses in area CA2 pyramidal neurons (PNs). Parvalbumin-expressing basket cells were largely responsible for the feedforward inhibitory drive of SuM over area C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…We tested whether depolarization of CA2 pyramidal neurons could induce LTP at SuM-CA2 pyramidal neuron synapses. In agreement with recent reports ( 13 , 41 ), light activation of the SuM fibers evoked oEPSCs recorded from CA2 pyramidal neurons (19.4 ± 3.4 pA, n = 10) ( Fig. 3 E and F ).…”
Section: Resultssupporting
confidence: 93%
“…We tested whether depolarization of CA2 pyramidal neurons could induce LTP at SuM-CA2 pyramidal neuron synapses. In agreement with recent reports ( 13 , 41 ), light activation of the SuM fibers evoked oEPSCs recorded from CA2 pyramidal neurons (19.4 ± 3.4 pA, n = 10) ( Fig. 3 E and F ).…”
Section: Resultssupporting
confidence: 93%
“…For the rest of this study, we performed whole-cell recordings from visually identified tdTomato + cells in the central CA2 ( Dudek et al, 2016 ), using both male and female adult animals. Characterization of intrinsic membrane properties was also performed at the beginning of each recording for further validation of typical CA2 PYR features by electrophysiological criteria ( Chevaleyre and Siegelbaum, 2010 ; Hitti and Siegelbaum, 2014 ; Tirko et al, 2018 ; Robert et al, 2020 , 2021 ). Alexa Fluor 633 dye was included in the internal solution for some recordings when post hoc recognition was needed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SuM neurons have been shown to project to the hippocampus, specifically the hippocampal CA2 in mice 31,49 . Here, we set to confirm if SuM⍰CA2 projections also exist in rats and to determine if OXTRs are specifically expressed in these projecting neurons.…”
Section: Resultsmentioning
confidence: 99%